The Influence Of Experience And Work Wages On The Productivity Of Mandar Silk Sarong Craftmen in Polman Regency - Muhammad Fahreza, Andi; Halim, Didin; Rivai, Andi Muhammad; Akbar, Fatimah (Universitas Negeri Makassar, 2025)
Wages are adjusted according to the results that have been given by employees to the company. Wage levels that are not sufficient for the living needs of employees will affect the difficulty of achieving optimal work productivity. Siagian in Sutrisno (2011), stated that the problem of work productivity can be seen as a behavioral problem, but it can also contain technical aspects.Wages are adjusted according to the results that have been givenemployees to the company. Insufficient wage levelsthe living needs of employees will affect the difficulty of achieving optimal work productivity. The higher the achievement, the greater the wages that will be received. Wages are essentially a means of equal distribution in all types and forms of wages. However, the distribution of wages for each position must be the same based on the number of products produced. For the employees themselves, the wages they receive have an important meaning in their lives, namely in accordance with the goals of employees working to earn a decent life.One of the problems in Polman district, West Sulawesi province, is regarding wages, focusing on the level of weaving experience, business status, type of yarn, and market availability. The problems that exist in the Mandar silk sarong craftsmen are focused on the level of wages for the workers of the Mandar silk sarong craftsmen themselves, including that almost all workers who work as Mandar silk sarong craftsmen get paid less than what they do. This is based on wage conditions determined by agents who will buy, then re-market by looking at the quality of the materials from the motives they work on. If the sarong motif has a low level of difficulty with imported Indian materials, the estimated wage earned is Rp. 70,000 – Rp. 150,000 per sarong. For the sarong motif with high difficulty using local materials, the estimated wage is Rp. 250,000 – Rp. 300,000 per month. The mandar silk sarong craftsmen can earn Rp. 1,500,000 per month from weaving 5-6 sarongs.